Dengue virus type 3 in Malaysia: Diversity, origin, and spread / Tan Kim Kee - Tan, Kim Kee (2018)
Dengue is a febrile disease with a tendency to result in intravascular leakages with severe outcomes and death if improperly managed. It is caused by any of the four known dengue virus (DENV) serotypes. DENV type 1 (DENV1), DENV type 2 (DENV2), and DENV type 3 (DENV3) are three DENV serotypes known to contribute to the recurring dengue outbreaks in Malaysia. In the current study, we examined the evolutionary genetics of DENV3 isolated in Malaysia for the past three decades to investigate the diversity, origin, and spread of the virus in the context of the recurring dengue outbreaks. To achieve the objective, we examined the dengue cases seen at the University Malaya Medical Centre (UMMC), a referral teaching hospital located at the boundary of Selangor and Federal Territory of Kuala Lumpur between 1981 and 2016. The state of Selangor and the Federal Territory of Kuala Lumpur (Klang Valley) contribute to more than 60% of the total dengue cases in Malaysia. The trend in the number of dengue cases observed at the UMMC paralleled that of the whole country. The complete genomes of DENV3 strains recovered in UMMC were sequenced. This was done to determine the genetic diversity of DENV3 recovered in the Klang Valley within the study period between 1987 and 2012. Subsequently, the phylogenetic and phylogeographic relationships of the DENV3 strains recovered in Klang Valley against other DENV3 strains recovered globally were examined. Virus neutralization assay was then performed using sera of patients with homotypic (DENV3) or heterotypic infection (DENV1 and DENV2) against the dominant circulating DENV3 genotypes to determine the influence of preexisting population immunity on DENV emergence and transmission locally at genotype level. At least three dengue outbreak cycles involving DENV3, DENV1, and DENV2 in that order of appearance (DENV3/DENV1/DENV2) were revealed during the study period. A iv disruption of this DENV3/DENV1/DENV2 sequential outbreak cycle was noted after 2002. The DENV3 genotype II (DENV3/II) was the predominant DENV3 that circulated between 1987 and 2002. After that, there was a switch of DENV3 genotype from long circulating DENV3/II to DENV3 genotype I (DENV3/I) after 2002 followed by DENV3 genotype III (DENV3/III) after 2008. No specific DENV3 genotype had sustained its transmission in the Klang Valley over the 20-year period. Phylogeography results further suggested repeated introductions of DENV3 genotypes of the Asian origin into Klang Valley sustained the persistent presence of different DENV3 genotypes over time. Results of virus neutralization assay further suggested that the pre-existing homotypic immunity against DENV3 and heterotypic immunity against DENV1 and DENV2 influenced the transmission of DENV3 in the Klang Valley. It was noted that DENV3/III, which emerged in 2008 was sensitive to homotypic immunity (DENV3) and heterotypic DENV1 immunity but not DENV2 immunity. The DENV2 cases in Klang valley increased after 2012 may have created an environment where the population has high DENV2 immunity. The DENV3/III is less sensitive to DENV2 immunity; therefore, it may have a greater potential in causing the next major DENV3 outbreak in the Klang Valley. Findings from the study could be a basis to initiate a study to determine the potential impact of widespread usage of dengue vaccines on the evolution of dengue viruses, especially in dengue endemic regions.